REPRESENTASI PENGETAHUAN PRAJURIT SATGAS TIMIKA TERHADAP PENCEGAHAN KEKAMBUHAN MALARIA BERULANG DI DETASEMEN MATRA 2 KOPASGAT - Priasmoro, Dian Pitaloka; Amelia, Zahwa (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Malaria recurrence is characterized by a state of the body that experiences several symptoms, such as fever, joint pain, and is caused by parasites that survive in the liver over several months or years. Malaria is commonly found in endemic areas, so soldiers assigned to these areas are very vulnerable to contracting the disease or experiencing a relapse. knowledge related to how to prevent recurrence. This study aims to evaluate the understanding of post-task force soldiers about malaria recurrence in Detachment Matra 2 Kopasgat. Methods: The research design used was a descriptive cross-sectional design. The population was post-task force soldiers affected by malaria at Detachment Matra 2. The sampling used was total sampling. The sample amounted to 40 people. The variable in this study was the description of knowledge about malaria prevention in soldiers of Detachment Matra 2. The measuring instrument used a questionnaire. Data were collected employing questionnaires, observation, and documentation. The research was conducted on May 31, 2024. Results: the results showed that almost half of the respondents experienced a lack of knowledge, with 16 respondents with a percentage of 40% and a small percentage experienced a low level of knowledge as many as 10 respondents with a percentage of 25%. Conclusion: variations in knowledge in soldiers can be influenced by several factors such as age, education, and the information that soldiers have received. For this reason, commitment and continuous education from both the institution and health services, such as hospitals, are needed to provide regular health promotion.